Appraising Herbicide Tank Mixtures for Weed Suppression, Crop Safety and Net Returns in Wheat (Journal of Agriculture and Biology, 2025)
Wheat is a staple crop in Pakistan but susceptible to yield losses from weeds infestations. Weeds compete with wheat for vital resources such as nutrients, water and sunlight leading to substantial economic losses in wheat production. The chemical control is widely adopted due to its efficiency although excessive and improper use of herbicide can lead to persistence in the soil, promote herbicide resistance and result in diverse weed flora in wheat fields. The implication of herbicide mixtures with multiple mode of action is recommended to enhance weed control efficacy and delay resistance development. In this study a field experiment was conducted by following a Randomized Complete Block Design (RCBD) with three replications and a plot size of 8 m × 3 m. A total nine treatments were applied including herbicide mixtures viz. T1= Atlantis (Iodo + Mesosulfuron) at 14.4 g a.i ha-1 WDG + Buctril Super (Bromxynil+MCPA) at 148.2 g a.i ha-1 EC, T2= Skopik Gold (Florasulam+Mesosulfuron) 14.8 g a.i ha-1 OD T3= Metafin Super (Tribenuron+metsulfuron) 70.642 g a.i ha-1 WDG + Maitu (Clodinafop propargyl+ Flucarbazone sodium) at 32.11 a.i g ha-1 OD T4= Trivax Super (Fluroxypyr+ Florasulam+ MCPA) at 1185.6 a.i ha-1 SC T5= Trivax Ultra (Mesosulfuron+ Florasulam+ MCPA) at 112.5 g a.i ha-1 OD T6= Buctril Super (Bromxynil+MCPA) at 148.2 g a.i ha-1 EC, + Maitu (Clodinafop propargyl+ Flucarbazone sodium) 32.11 a.i g ha-1 OD T7= Buctril Super (Bromxynil+MCPA) at 148.2 g a.i ha-1 EC, + Axial (Pinoxaden) at 41.25 g a.i ha-1 EC T8= Wheat Star (Clopyralid+Fluroxypyr+ Tribenuron) 244.53 g a.i ha-1 WDG, + Axial (Pinoxaden) at 41.25 g a.i ha-1 EC T9= Weedy Check. The treatment Metafin Super in combination with Maitu produced the highest grain yield (4401.0 kg ha-1), biological yield (9334.1 kg ha-1) and spike length (13.19 cm). Additionally, the application of Skopik Gold resulted in the highest harvest index (61.73%), 1000-seed weight (46.75g) and suppressed the weeds showing a least density of 10.0 and 8.67 plants m-2 at 30 and 60 days after treatment, respectively as compared to weedy check. The finding of this study concluded that mixture of Florasulam+Mesosulfuron was effective in controlling the weed population that could reduce the yield gaps owing to weed competition in wheat.